Lithium metal composite negative electrode based on one-dimensional nanoreactor and preparation method of lithium metal composite negative electrode

By using a one-dimensional nanoreactor and anionic catalyst in the lithium metal composite anode, a stable SEI layer is formed and the catalyst is isolated, and the problems of uneven deposition of the lithium metal anode and anionic catalyst consumption are solved, and a lithium metal battery with high cycle stability and safety is achieved.

CN119560503AActive Publication Date: 2025-03-04GUANGDONG UNIV OF TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411446646.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-03-04
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The lithium metal negative electrode has uneven deposition and volume expansion during the plating/peeling process, resulting in uncontrollable growth of lithium dendrites and rupture of the SEI layer, which in turn causes short circuits, heating and explosion problems within the battery. At the same time, anionic catalyst is consumed during the battery cycle, making it difficult to produce on a large scale and is costly.

Method used

A lithium metal composite anode based on a one-dimensional nanoreactor is used to roll-compress the metal lithium substrate with a self-supporting nanofiber. The anion catalyst is coated in the core layer of the one-dimensional nanoreactor to form a SEI layer rich in inorganic species such as LiF, Li3N and Li2S, which inhibits the growth of lithium dendrites and isolates the anion catalyst through the shell to avoid unnecessary electrochemical reactions.

Benefits of technology

It effectively alleviates the uneven deposition and volume expansion of lithium metal negative electrodes, inhibits the growth of lithium dendrites, improves the cycle stability and safety of the battery, reduces the consumption of anionic catalysts, reduces production costs, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560503A_ABST
    Figure CN119560503A_ABST
Patent Text Reader

Abstract

The invention relates to a lithium metal composite negative electrode based on a one-dimensional nanoreactor and a preparation method of the lithium metal composite negative electrode. The lithium metal composite negative electrode based on the one-dimensional nanoreactor is formed by rolling and compounding a metal lithium substrate and self-supporting nanofibers; the self-supporting nanofiber comprises a plurality of one-dimensional nanoreactors; the one-dimensional nanoreactor comprises a core layer and a shell layer arranged outside the core layer in a sleeving mode, the core layer is a hollow layer in which an anion catalyst is dispersed, and the shell layer is made of polymer fibers. In addition, the invention also provides a method for preparing nanofibers with a core-shell complex structure by using coaxial directional double-nozzle electrostatic spinning, a core layer is decomposed by calcining, hollow nanofibers are manufactured, and an anion catalyst is dispersed and coated in the core layer of a one-dimensional nanoreactor, so that the problems that a lithium metal battery is poor in cycling stability, and the performance of the lithium metal battery is poor are solved. Moreover, unnecessary loss caused by extra electrochemical reaction of the anion catalyst in the charging and discharging process can be avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of lithium metal composite negative electrode materials, and in particular to a lithium metal composite negative electrode based on a one-dimensional nanoreactor and a preparation method thereof. Background Art

[0002] As an important electrochemical energy storage device, batteries have experienced more than a hundred years of development. So far, the energy density of graphite negative electrodes of lithium-ion batteries has gradually approached its theoretical limit. In the "Made in China 2025" issued by the State Council in 2015, it was proposed that the energy density of power battery cells in my country should reach 400Wh·kg by 2025. -1 , reaching 500Wh·kg in 2030 -1 Therefore, the main goal of current and future battery technology development is to accelerate the realization of commercial batteries with higher energy density and lower production costs while maintaining battery safety and reliability. The lithium metal anode, known as the "holy grail", is the most promising anode material for high-energy battery systems.

[0003] However, during the lithium ion plating / stripping process, the non-uniformity of lithium deposition and unlimited volume expansion of the lithium metal negative electrode will cause the uncontrollable growth of lithium dendrites and the rupture of the SEI layer, thereby piercing the diaphragm, causing internal short circuits in the battery, heating, and even fire and explosion. In addition, the large specific surface area of ​​lithium dendrites will expose more active lithium to the electrolyte, aggravating the continuous occurrence of side reactions, causing a large amount of inactive lithium to accumulate, and bringing serious polarization. Therefore, one of the keys to building a long-life, high-safety lithium metal secondary battery is to inhibit the dendritic growth of metallic lithium.

[0004] Studies have shown that applying anionic catalysts to lithium metal battery separators can effectively improve the electrochemical performance of lithium metal batteries. However, during the battery cycle, anionic catalysts are always consumed by unnecessary electrochemical reactions, and the preparation process is difficult to scale up and the cost is high, which still needs to be solved. Summary of the invention

[0005] Based on this, the purpose of the present invention is to provide a lithium metal composite negative electrode based on a one-dimensional nanoreactor and a preparation method thereof, which can effectively alleviate the dendritic growth of metallic lithium caused by the uneven lithium deposition and unlimited volume expansion of the lithium metal negative electrode, and reduce the consumption of anion catalysts during the battery cycle.

[0006] A method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor, which is formed by rolling and compounding a metal lithium substrate and a self-supporting nanofiber; the self-supporting nanofiber includes a plurality of one-dimensional nanoreactors; the one-dimensional nanoreactor includes a core layer and a shell layer sleeved outside the core layer, the core layer is a hollow layer dispersed with an anion catalyst, and the shell layer is a polymer fiber.

[0007] The lithium metal composite negative electrode based on a one-dimensional nanoreactor of the present invention encapsulates an anion catalyst in the core layer of the one-dimensional nanoreactor. When the anion catalyst is subjected to mechanical stress caused by volume deformation, it will generate a built-in electric field to reduce the diffusion barrier of nearby lithium ions, while capturing anions to destroy their electronic structure, forming an SEI layer rich in inorganic species such as LiF, Li3N and Li2S, thereby inhibiting the growth of lithium dendrites, solving the poor cycle stability, thermal runaway and a series of safety problems of lithium metal batteries. In addition, the one-dimensional nanoreactor shell can isolate the anion catalyst from the lithium substrate while providing physical protection for the diaphragm, avoiding unnecessary loss of the anion catalyst caused by additional electrochemical reactions during the charge and discharge process.

[0008] Furthermore, the anion catalyst includes one or more of barium titanate, palladium titanate, lead titanate, lead zirconate titanate, calcium silicate, aluminum silicate, lead niobate, strontium niobate, barium niobate, potassium niobate, sodium niobate, sodium metaniobate, potassium metaniobate, calcium germanate, barium germanate, titanium germanate, potassium tantalate, and bismuth aluminate.

[0009] The method for preparing the lithium metal composite negative electrode based on the one-dimensional nanoreactor comprises the following specific steps:

[0010] (1) Preparation of a core layer precursor spinning solution: dispersing an anion catalyst in a first solvent, then adding polymer A and stirring to uniformly mix to obtain the core layer precursor spinning solution;

[0011] (2) Preparation of a shell layer precursor spinning solution: dissolving polymer B in a second solvent, stirring, and mixing uniformly to obtain the shell layer precursor spinning solution;

[0012] (3) Preparation of precursor nanofibers: using coaxial electrospinning technology, the core layer precursor spinning solution and the shell layer precursor spinning solution in steps (1) and (2) are respectively loaded into medical syringes and placed on a micro-injection pump, and the micro-injection pump is started to push the core layer precursor spinning solution and the shell layer precursor spinning solution forward and are stretched from the double nozzle needle to the rotating receiving roller under the action of the electric field force to obtain the precursor nanofibers;

[0013] (4) Preparation of self-supporting nanofibers: pre-oxidizing and annealing the precursor nanofibers obtained in step (3) to obtain the self-supporting nanofibers;

[0014] (5) Preparation of lithium metal composite negative electrode: The self-supporting nanofibers obtained in step (4) are rolled together with lithium sheets to form the lithium metal composite negative electrode.

[0015] The present invention utilizes coaxial directional double-nozzle electrospinning to prepare nanofibers with a complex core-shell structure, achieves precise control of different layers, and simultaneously calcines and decomposes the core layer to manufacture hollow nanofibers and disperse the anionic catalyst in the core layer. The process is simple, green and efficient, suitable for large-scale production, and has excellent application prospects.

[0016] Furthermore, the specific rolling step of step (5) includes: first rolling the lithium sheet 0 to 10 times, and then stacking the self-supporting nanofibers obtained in step (4) and the lithium sheet together and rolling them to form the lithium metal composite negative electrode with a thickness of 50 to 250 μm.

[0017] Furthermore, the mass percentage concentration of the anion catalyst in step (1) is 2-30wt%, the mass percentage concentration of the polymer A is 10-30wt%; and the mass percentage concentration of the polymer B in step (2) is 5-15wt%.

[0018] Furthermore, the polymer A includes one or more of polymethyl methacrylate, polystyrene, and polyvinyl pyrrolidone.

[0019] Furthermore, the polymer B includes one or more of polyacrylonitrile, polypyrrole, polyamide, urea, melamine, and asphalt.

[0020] Furthermore, the first solvent and the second solvent include one or more of deionized water, ethanol, acetone, ethylene glycol, N,N-dimethylformamide, petroleum ether, and tetrahydrofuran.

[0021] Furthermore, the process parameters of the electrospinning in step (3) are as follows: the distance from the double nozzle needle to the rotating receiving roller is 15 to 20 cm, and the injection speed of the spinning solution is 1 to 2 mL·h -1 The rotating speed of the rotating receiving roller is 300-500 r / min. -1 , voltage is 15~23kV, ambient temperature is 20~50℃, and ambient humidity is 10~40%.

[0022] Furthermore, in step (4), the pre-oxidation temperature is 270-300°C, the time is 1-2h, and the heating rate is 1-5°C·min -1 .

[0023] For better understanding and implementation, the present invention is described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic structural diagram of the lithium metal composite negative electrode based on the one-dimensional nanoreactor according to the present invention;

[0025] Figure 2 The present invention is a flow chart of the preparation method of the lithium metal composite negative electrode based on the one-dimensional nanoreactor. DETAILED DESCRIPTION

[0026] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the embodiments of the present application. It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the embodiments of the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the embodiments of the present application.

[0027] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the embodiments of the present application. The singular forms of "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings. In addition, in the description of the present application, unless otherwise specified, "plurality" refers to two or more.

[0028] The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present application. Instead, they are only examples of devices and methods consistent with some aspects of the present application as detailed in the appended claims.

[0029] It should be understood that the embodiments of the present application are not limited to the precise structures described above and shown in the drawings, and various modifications and changes can be made without departing from the scope thereof.

[0030] See also Figure 1 The lithium metal composite negative electrode based on a one-dimensional nanoreactor of the present invention is formed by rolling and compounding a metal lithium substrate and a self-supporting nanofiber; the self-supporting nanofiber includes a plurality of one-dimensional nanoreactors; the one-dimensional nanoreactor includes a core layer and a shell layer sleeved outside the core layer, the core layer is a hollow layer dispersed with an anion catalyst, and the shell layer is a polymer fiber. The mass percentage concentration of the anion catalyst is 2 to 30wt%; the anion catalyst includes one or more of barium titanate, palladium titanate, lead titanate, lead zirconate titanate, calcium silicate, aluminum silicate, lead niobate, strontium niobate, barium niobate, potassium niobate, sodium niobate, sodium metaniobate, potassium metaniobate, calcium germanate, barium germanate, titanium germanate, potassium tantalate, and bismuth aluminate.

[0031] See also Figure 2 The method for preparing the lithium metal composite negative electrode based on the one-dimensional nanoreactor of the present invention comprises the following specific steps:

[0032] (1) Preparation of a core layer precursor spinning solution: dispersing an anion catalyst in a first solvent, then adding 10 to 30 wt% of polymer A, stirring at room temperature for 6 to 12 hours, and mixing uniformly to obtain the core layer precursor spinning solution; the polymer A includes one or more of polymethyl methacrylate, polystyrene, and polyvinyl pyrrolidone;

[0033] (2) Preparation of a shell precursor spinning solution: dissolving a polymer B having a mass percentage concentration of 5 to 15 wt % in a second solvent, stirring at room temperature for 6 to 12 hours, and mixing uniformly to obtain the shell precursor spinning solution; the polymer B includes one or more of polyacrylonitrile, polypyrrole, polyamide, urea, melamine, and asphalt;

[0034] The first solvent and the second solvent include one or more of deionized water, ethanol, acetone, ethylene glycol, N,N-dimethylformamide, petroleum ether, and tetrahydrofuran;

[0035] (3) Preparation of precursor nanofibers: Using coaxial electrospinning technology, the core layer precursor spinning solution and the shell layer precursor spinning solution in steps (1) and (2) are respectively loaded into medical syringes and placed on a micro-injection pump, and the micro-injection pump is started to push the core layer precursor spinning solution and the shell layer precursor spinning solution forward and are stretched from the double nozzle needle to the rotating receiving roller under the action of the electric field force to obtain precursor fibers; the distance from the double nozzle needle to the rotating receiving roller is 15 to 20 cm, and the spinning solution injection speed is 1 to 2 mL·h -1 The rotating speed of the rotating receiving roller is 300-500 r / min. -1 , voltage is 15~23kV, ambient temperature is 20~50℃, and ambient humidity is 10~40%.

[0036] (4) Preparation of self-supporting nanofibers: The precursor nanofibers obtained in step (3) are placed in a muffle furnace for pre-oxidation and annealing, wherein the pre-oxidation temperature is 270-300°C, the time is 1-2 hours, and the heating rate is 1-5°C·min -1 , obtaining the self-supporting nanofiber;

[0037] (5) Preparation of lithium metal composite negative electrode: The self-supporting nanofibers obtained in step (4) are rolled together with lithium sheets in a glove box to prepare a lithium metal composite negative electrode.

[0038] Example 1

[0039] A method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor comprises the following specific steps:

[0040] (1) Preparation of the core layer precursor spinning solution: 0.1 g of barium titanate (BaTiO3) was dispersed in 4 mL of N,N-dimethylformamide (DMF), and then 1.2 g of polymethyl methacrylate (PMMA) was added. The mixture was stirred at room temperature for 6 h and mixed evenly to obtain the core layer precursor spinning solution.

[0041] (2) Preparation of shell precursor spinning solution: 0.25 g of polyacrylonitrile (PAN) was dissolved in 5 mL of N,N-dimethylformamide (DMF), stirred at room temperature for 6 h, and mixed evenly to obtain the shell precursor spinning solution.

[0042] (3) Preparation of precursor nanofibers: Using coaxial electrospinning technology, the core layer precursor spinning solution and the shell layer precursor spinning solution in steps (1) and (2) are respectively loaded into medical syringes and placed on a micro-injection pump, and the micro-injection pump is started to push the core layer precursor spinning solution and the shell layer precursor spinning solution forward and are stretched from the double nozzle needle to the rotating receiving roller under the action of the electric field force to obtain the precursor nanofibers; wherein the process parameters of electrospinning are: the distance from the double nozzle needle to the rotating receiving roller is 15 cm, and the injection speed of the spinning solution is 1 mL·h -1 The rotating speed of the rotating receiving roller is 400 r / min. -1 , the voltage is 20kV, the ambient temperature is 30℃, and the ambient humidity is 10%.

[0043] (4) Preparation of self-supporting nanofibers: The precursor nanofibers obtained in step (3) were placed in a muffle furnace for pre-oxidation and annealing at a temperature of 270°C for 2 hours at a heating rate of 2°C min. -1 , a self-supporting nanofiber is obtained, which is composed of a one-dimensional nanoreactor consisting of a hollow layer with barium titanate (BaTiO3) dispersed in the core layer and polyacrylonitrile (PAN) as the shell layer.

[0044] (5) Preparation of lithium metal composite negative electrode: In a glove box, first roll-press 150 μm lithium sheets one by one until the thickness is reduced to 50 μm, then stack the self-supporting nanofibers obtained in step (4) and the lithium sheets together and roll-press them to make the lithium metal composite negative electrode with a thickness of 100 μm.

[0045] Example 2

[0046] A method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor comprises the following specific steps:

[0047] (1) Preparation of the core layer precursor spinning solution: 0.1 g of barium titanate (BaTiO3) was dispersed in 4 mL of N,N-dimethylformamide (DMF), and then 0.43 g of polymethyl methacrylate (PMMA) was added. The mixture was stirred at room temperature for 6 h and mixed evenly to obtain the core layer precursor spinning solution.

[0048] (2) Preparation of shell precursor spinning solution: 0.84 g polyacrylonitrile (PAN) was dissolved in 5 mL N,N-dimethylformamide (DMF), stirred at room temperature for 6 h, and mixed evenly to obtain the shell precursor spinning solution.

[0049] (3) Preparation of precursor nanofibers: Using coaxial electrospinning technology, the core layer precursor spinning solution and the shell layer precursor spinning solution in steps (1) and (2) are respectively loaded into medical syringes and placed on a micro-injection pump, and the micro-injection pump is started to push the core layer precursor spinning solution and the shell layer precursor spinning solution forward and are stretched from the double nozzle needle to the rotating receiving roller under the action of the electric field force to obtain the precursor nanofibers; wherein the process parameters of electrospinning are: the distance from the double nozzle needle to the rotating receiving roller is 15 cm, and the injection speed of the spinning solution is 1 mL·h -1 The rotating speed of the rotating receiving roller is 400 r / min. -1 , the voltage is 20kV, the ambient temperature is 30℃, and the ambient humidity is 10%.

[0050] (4) Preparation of self-supporting nanofibers: The precursor nanofibers obtained in step (3) were placed in a muffle furnace for pre-oxidation and annealing at a temperature of 280°C for 2 hours at a heating rate of 2°C min. -1 , a self-supporting nanofiber is obtained, which is composed of a one-dimensional nanoreactor consisting of a hollow layer with barium titanate (BaTiO3) dispersed in the core layer and polyacrylonitrile (PAN) as the shell layer.

[0051] (5) Preparation of lithium metal composite negative electrode: same as Example 1.

[0052] Example 3

[0053] A method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor comprises the following specific steps:

[0054] (1) Preparation of the core layer precursor spinning solution: 1.2 g of barium titanate (BaTiO3) was dispersed in 4 mL of N,N-dimethylformamide (DMF), and then 2.1 g of polymethyl methacrylate (PMMA) was added. The mixture was stirred at room temperature for 12 h and mixed evenly to obtain the core layer precursor spinning solution.

[0055] (2) Preparation of shell precursor spinning solution: 0.5 g of polyacrylonitrile (PAN) was dissolved in 5 mL of N,N-dimethylformamide (DMF), stirred at room temperature for 12 h, and mixed evenly to obtain the shell precursor spinning solution.

[0056] (3) Preparation of precursor nanofibers: Using coaxial electrospinning technology, the core layer precursor spinning solution and the shell layer precursor spinning solution in steps (1) and (2) are respectively loaded into medical syringes and placed on a micro-injection pump, and the micro-injection pump is started to push the core layer precursor spinning solution and the shell layer precursor spinning solution forward and are stretched from the double nozzle needle to the rotating receiving roller under the action of the electric field force to obtain the precursor nanofibers; wherein the process parameters of electrospinning are: the distance from the double nozzle needle to the rotating receiving roller is 18 cm, and the injection speed of the spinning solution is 1 mL·h -1 The rotating speed of the rotating receiving roller is 400 r / min. -1 , the voltage is 20kV, the ambient temperature is 30℃, and the ambient humidity is 20%.

[0057] (4) Preparation of self-supporting nanofibers: The precursor nanofibers obtained in step (3) were placed in a muffle furnace for pre-oxidation and annealing at a temperature of 280°C for 2 hours at a heating rate of 2°C min. -1 , a self-supporting nanofiber is obtained, which is composed of a one-dimensional nanoreactor consisting of a hollow layer with barium titanate (BaTiO3) dispersed in the core layer and polyacrylonitrile (PAN) as the shell layer.

[0058] (5) Preparation of lithium metal composite negative electrode: same as in Example 1.

[0059] Example 4

[0060] A method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor comprises the following specific steps:

[0061] (1) Preparation of core layer precursor spinning solution: same as Example 3.

[0062] (2) Preparation of shell precursor spinning solution: same as Example 3.

[0063] (3) Preparation of precursor nanofibers: Using coaxial electrospinning technology, the core layer precursor spinning solution and the shell layer precursor spinning solution in steps (1) and (2) are respectively loaded into medical syringes and placed on a micro-injection pump, and the micro-injection pump is started to push the core layer precursor spinning solution and the shell layer precursor spinning solution forward and are stretched from the double nozzle needle to the rotating receiving roller under the action of the electric field force to obtain the precursor nanofibers; wherein the process parameters of electrospinning are: the distance from the double nozzle needle to the rotating receiving roller is 20 cm, and the injection speed of the spinning solution is 2 mL·h -1 The rotating speed of the rotating receiving roller is 500 r / min -1 , the voltage is 23kV, the ambient temperature is 50℃, and the ambient humidity is 10%.

[0064] (4) Preparation of self-supporting nanofibers: The precursor nanofibers obtained in step (3) were placed in a muffle furnace for pre-oxidation and annealing at a temperature of 280°C for 2 hours at a heating rate of 2°C min. -1 , a self-supporting nanofiber is obtained, which is composed of a one-dimensional nanoreactor consisting of a hollow layer with barium titanate (BaTiO3) dispersed in the core layer and polyacrylonitrile (PAN) as the shell layer.

[0065] (5) Preparation of lithium metal composite negative electrode: same as Example 1.

[0066] Example 5

[0067] A method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor comprises the following specific steps:

[0068] (1) Preparation of the core layer precursor spinning solution: 0.3 g of barium titanate (BaTiO3) was dispersed in 2 mL of N,N-dimethylformamide (DMF), and then 0.2 g of polymethyl methacrylate (PMMA) was added. The mixture was stirred at room temperature for 6 h and mixed evenly to obtain the core layer precursor spinning solution.

[0069] (2) Preparation of shell precursor spinning solution: 0.5 g of polyacrylonitrile (PAN) was dissolved in 3 mL of N,N-dimethylformamide (DMF), stirred at room temperature for 6 h, and mixed evenly to obtain the shell precursor spinning solution.

[0070] (3) Preparation of precursor nanofibers: Using coaxial electrospinning technology, the core layer precursor spinning solution and the shell layer precursor spinning solution in steps (1) and (2) are respectively loaded into medical syringes and placed on a micro-injection pump, and the micro-injection pump is started to push the core layer precursor spinning solution and the shell layer precursor spinning solution forward and are stretched from the double nozzle needle to the rotating receiving roller under the action of the electric field force to obtain the precursor nanofibers; wherein the process parameters of electrospinning are: the distance from the double nozzle needle to the rotating receiving roller is 15 cm, and the injection speed of the spinning solution is 1 mL·h -1 The rotating speed of the receiving roller is 300 r / min. -1 , the voltage is 15kV, the ambient temperature is 50℃, and the ambient humidity is 10%.

[0071] (4) Preparation of self-supporting nanofibers: The precursor nanofibers obtained in step (3) were placed in a muffle furnace for pre-oxidation and annealing at a temperature of 280°C for 2 hours at a heating rate of 2°C min. -1 , a self-supporting nanofiber is obtained, which is composed of a one-dimensional nanoreactor consisting of a hollow layer with barium titanate (BaTiO3) dispersed in the core layer and polyacrylonitrile (PAN) as the shell layer.

[0072] (5) Preparation of lithium metal composite negative electrode: same as Example 1.

[0073] Example 6

[0074] A method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor comprises the following specific steps:

[0075] (1) Preparation of the core layer precursor spinning solution: 1.2 g of barium titanate (BaTiO3) was dispersed in 8 mL of N,N-dimethylformamide (DMF), and then 2.4 g of polymethyl methacrylate (PMMA) was added. The mixture was stirred at room temperature for 12 h and mixed evenly to obtain the core layer precursor spinning solution.

[0076] (2) Preparation of shell precursor spinning solution: 1 g of polyacrylonitrile (PAN) was dissolved in 10 mL of N,N-dimethylformamide (DMF), stirred at room temperature for 12 h, and mixed evenly to obtain the shell precursor spinning solution.

[0077] (3) Preparation of precursor nanofibers: Using coaxial electrospinning technology, the core layer precursor spinning solution and the shell layer precursor spinning solution in steps (1) and (2) are respectively loaded into medical syringes and placed on a micro-injection pump, and the micro-injection pump is started to push the core layer precursor spinning solution and the shell layer precursor spinning solution forward and are stretched from the double nozzle needle to the rotating receiving roller under the action of the electric field force to obtain the precursor nanofibers; wherein the process parameters of electrospinning are: the distance from the double nozzle needle to the rotating receiving roller is 18 cm, and the injection speed of the spinning solution is 1 mL·h -1 The rotating speed of the rotating receiving roller is 400 r / min. -1 , the voltage is 20kV, the ambient temperature is 30℃, and the ambient humidity is 40%.

[0078] (4) Preparation of self-supporting nanofibers: The precursor nanofibers obtained in step (3) were placed in a muffle furnace for pre-oxidation and annealing at a temperature of 280°C for 2 hours at a heating rate of 5°C min. -1 , a self-supporting nanofiber is obtained, which is composed of a one-dimensional nanoreactor consisting of a hollow layer with barium titanate (BaTiO3) dispersed in the core layer and polyacrylonitrile (PAN) as the shell layer.

[0079] (5) Preparation of lithium metal composite negative electrode: In a glove box, the self-supporting nanofibers obtained in step (4) are directly stacked together with a 150 μm lithium sheet and rolled to produce the lithium metal composite negative electrode with a thickness of 250 μm.

[0080] Example 7

[0081] A method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor comprises the following specific steps:

[0082] (1) Preparation of core layer precursor spinning solution: same as Example 3.

[0083] (2) Preparation of shell precursor spinning solution: same as Example 3.

[0084] (3) Preparation of precursor nanofibers: same as Example 3.

[0085] (4) Preparation of self-supporting nanofibers: The precursor nanofibers obtained in step (3) were placed in a muffle furnace for pre-oxidation and annealing at a temperature of 300°C for 1 h at a heating rate of 1°C min. -1 , a self-supporting nanofiber is obtained, which is composed of a one-dimensional nanoreactor consisting of a hollow layer with barium titanate (BaTiO3) dispersed in the core layer and polyacrylonitrile (PAN) as the shell layer.

[0086] (5) Preparation of lithium metal composite negative electrode: same as Example 3.

[0087] Comparative Example 1

[0088] A method for preparing a lithium metal composite negative electrode comprises the following specific steps:

[0089] (1) Preparation of the core layer precursor spinning solution: 1.2 g of polymethyl methacrylate (PMMA) was dissolved in 4 mL of N,N-dimethylformamide (DMF), stirred at room temperature for 12 h, and mixed evenly to obtain the core layer precursor spinning solution.

[0090] (2) Preparation of shell precursor spinning solution: 0.5 g of polyacrylonitrile (PAN) was dissolved in 5 mL of N,N-dimethylformamide (DMF), stirred at room temperature for 12 h, and mixed evenly to obtain the shell precursor spinning solution.

[0091] (3) Preparation of precursor nanofibers: Using coaxial electrospinning technology, the core layer precursor spinning solution and the shell layer precursor spinning solution in steps (1) and (2) are respectively loaded into medical syringes and placed on a micro-injection pump, and the micro-injection pump is started to push the core layer precursor spinning solution and the shell layer precursor spinning solution forward and are stretched from the double nozzle needle to the rotating receiving roller under the action of the electric field force to obtain the precursor nanofibers; wherein the process parameters of electrospinning are: the distance from the double nozzle needle to the rotating receiving roller is 18 cm, and the injection speed of the spinning solution is 1 mL·h -1 The rotating speed of the rotating receiving roller is 400 r / min. -1 , the voltage is 20kV, the ambient temperature is 30℃, and the ambient humidity is 20%.

[0092] (4) Preparation of self-supporting nanofibers: The precursor nanofibers obtained in step (3) were placed in a muffle furnace for pre-oxidation and annealing at a temperature of 280°C for 2 hours at a heating rate of 2°C min. -1 , a self-supporting nanofiber is obtained, which is composed of a one-dimensional nanoreactor consisting of a hollow layer with barium titanate (BaTiO3) dispersed in the core layer and polyacrylonitrile (PAN) as the shell layer.

[0093] (5) Preparation of lithium metal composite negative electrode: In a glove box, first roll-press 150 μm lithium sheets one by one until the thickness is reduced to 50 μm, then stack the self-supporting nanofibers obtained in step (4) and the lithium sheets together and roll-press them to make the lithium metal composite negative electrode with a thickness of 100 μm.

[0094] Comparative Example 2

[0095] A method for preparing a lithium metal negative electrode comprises the following specific steps: in a glove box, 150 μm lithium sheets are rolled one by one to prepare a lithium metal negative electrode with a thickness of 100 μm.

[0096] The negative electrodes of the above-mentioned Examples 1 to 7 and Comparative Examples 1 to 2 were assembled into symmetrical cells: the prepared negative electrodes were cut and used as counter electrodes and working electrodes to assemble symmetrical cells, the button cell model was CR2032, the separator was a polypropylene microporous membrane Celgard2400, and the electrolyte was LiTFSI / DOL+DME (V / V=1:1) containing 2wt% LiNO3. The assembled symmetrical cells were tested for electrochemical performance on a Newway test system, and the test conditions were 1 mA·cm -2 , 1mAh·cm -2 , the results are shown in Table 1.

[0097] Table 1 Symmetrical battery test results

[0098]

[0099] The negative electrodes of the above-mentioned embodiments 1 to 7 and comparative examples 1 to 2 were assembled with lithium iron phosphate into a full battery: lithium iron phosphate, superconducting carbon black (SuperP) and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 8:1:1, and then an appropriate amount of N-methylpyrrolidone (NMP) was added, and the mixture was fully stirred into a paste. The mixed slurry was evenly coated on aluminum foil with a scraper, and then placed in a vacuum drying oven at 60°C for 12 hours, and cut as a positive electrode of a lithium metal battery; in a glove box, the negative electrode was cut and prepared, and then the full battery was assembled. The battery model was CR2032, the diaphragm was a polypropylene microporous membrane Celgard2400, and the electrolyte was LiTFSI / DOL+DME (V / V=1:1) containing 2wt% LiNO3. The assembled symmetrical battery was subjected to electrochemical performance testing on the Xinwei test system, and the results are shown in Table 2.

[0100] Table 2 Full battery test results

[0101]

[0102] From the symmetrical battery test results in Table 1, it can be seen that the first deposition nucleation overvoltage (mV) of Comparative Examples 1 to 2 is much higher than that of Examples 1 to 7 of the present application, which may lead to uneven deposition of lithium metal and form a lithium dendrite structure, which will increase the risk of internal short circuit of the battery and affect the safety and cycle stability of the battery; in addition, the first deposition nucleation overvoltage (mV) of Comparative Examples 1 to 2 is much higher than that of Examples 1 to 7 of the present application, which will lead to uneven chemical reactions inside the battery, thereby causing degradation and deterioration of the battery, and will also increase the internal resistance of the battery, affecting the energy conversion efficiency, thereby reducing the battery performance and service life. Compared with Comparative Examples 1 to 2, the polarization voltage of the symmetrical battery of Examples 1 to 7 of the present invention is smaller and the cycle life is longer, indicating that the composite negative electrode can effectively enhance the diffusion rate of ions at the electrode interface, alleviate the polarization phenomenon during lithium deposition, and alleviate the growth of lithium dendrites.

[0103] From the full battery test results in Table 2, it can be seen that the discharge specific capacity (mAh / g) and capacity retention rate (%) of Comparative Examples 1 to 2 after 500 cycles of 1C are much lower than those of Examples 1 to 7 of the present application, indicating that the negative electrode of Comparative Examples 1 to 2 and lithium iron phosphate are assembled into a full battery with poor cycle stability and short service life. Compared with Comparative Examples 1 to 2, the capacity decay of Examples 1 to 7 of the present invention under 1C conditions is relatively slow, and the cycle stability is better, mainly because the ion diffusion rate at the interface of the composite negative electrode is high, and the formed SEI membrane has fast ion transmission and strong mechanical properties. In addition, the one-dimensional nanoreactor shell protects the anion catalyst, avoiding unnecessary loss of the anion catalyst during the charge and discharge process, thereby extending the life of the lithium metal battery.

[0104] The lithium metal composite negative electrode based on a one-dimensional nanoreactor of the present invention uses coaxial directional double nozzle electrospinning to prepare nanofibers with a complex core-shell structure, and simultaneously calcines and decomposes the core layer to manufacture hollow nanofibers and disperse anion catalysts in the core layer, and coats the anion catalysts in the core layer of the one-dimensional nanoreactor. During the battery cycle, a stable SEI layer rich in inorganic species such as LiF, Li3N and Li2S is formed, thereby increasing the ion diffusion rate, inhibiting the growth of lithium dendrites, and improving the performance and safety of the battery. In addition, the one-dimensional nanoreactor shell layer can also isolate the anion catalyst from the lithium substrate while providing physical protection for the diaphragm, avoiding unnecessary losses caused by additional electrochemical reactions during the charge and discharge process. And the preparation method of the lithium metal composite negative electrode based on the one-dimensional nanoreactor is simple in steps, green and efficient, suitable for large-scale production, and has excellent application prospects.

[0105] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.

Claims

1. A lithium metal composite negative electrode based on a one-dimensional nanoreactor, characterized in that: It is formed by rolling and compounding a metal lithium substrate and self-supporting nanofibers; the self-supporting nanofibers include a number of one-dimensional nanoreactors; the one-dimensional nanoreactor includes a core layer and a shell layer sleeved outside the core layer, the core layer is a hollow layer dispersed with an anion catalyst, and the shell layer is a polymer fiber.

2. The lithium metal composite negative electrode based on a one-dimensional nanoreactor according to claim 1, characterized in that: The anion catalyst includes one or more of barium titanate, palladium titanate, lead titanate, lead zirconate titanate, calcium silicate, aluminum silicate, lead niobate, strontium niobate, barium niobate, potassium niobate, sodium niobate, sodium metaniobate, potassium metaniobate, calcium germanate, barium germanate, titanium germanate, potassium tantalate, and bismuth aluminate.

3. The method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor according to any one of claims 1 to 2, characterized in that: The specific steps include: (1) Preparation of a core layer precursor spinning solution: dispersing an anion catalyst in a first solvent, then adding polymer A and stirring to uniformly mix to obtain the core layer precursor spinning solution; (2) Preparation of a shell layer precursor spinning solution: dissolving polymer B in a second solvent, stirring, and mixing uniformly to obtain the shell layer precursor spinning solution; (3) Preparation of precursor nanofibers: using coaxial electrospinning technology, the core layer precursor spinning solution and the shell layer precursor spinning solution in steps (1) and (2) are respectively loaded into medical syringes and placed on a micro-injection pump, and the micro-injection pump is started to push the core layer precursor spinning solution and the shell layer precursor spinning solution forward and are stretched from the double nozzle needle to the rotating receiving roller under the action of the electric field force to obtain the precursor nanofibers; (4) Preparation of self-supporting nanofibers: pre-oxidizing and annealing the precursor nanofibers obtained in step (3) to obtain the self-supporting nanofibers; (5) Preparation of lithium metal composite negative electrode: The self-supporting nanofibers obtained in step (4) are rolled together with lithium sheets to form the lithium metal composite negative electrode.

4. The method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor according to claim 3, characterized in that: The specific rolling step of step (5) includes: first rolling the lithium sheet 0 to 10 times, and then stacking the self-supporting nanofibers obtained in step (4) and the lithium sheet together for rolling to form the lithium metal composite negative electrode with a thickness of 50 to 250 μm.

5. The method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor according to claim 3, characterized in that: The mass percentage concentration of the anion catalyst in step (1) is 2 to 30 wt %; the mass percentage concentration of the polymer A is 10 to 30 wt %; and the mass percentage concentration of the polymer B in step (2) is 5 to 15 wt %.

6. The method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor according to claim 3, characterized in that: The polymer A includes one or more of polymethyl methacrylate, polystyrene and polyvinyl pyrrolidone.

7. The method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor according to claim 3, characterized in that: The polymer B includes one or more of polyacrylonitrile, polypyrrole, polyamide, urea, melamine and asphalt.

8. The method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor according to claim 3, characterized in that: The first solvent and the second solvent include one or more of deionized water, ethanol, acetone, ethylene glycol, N,N-dimethylformamide, petroleum ether, and tetrahydrofuran.

9. The method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor according to claim 3, characterized in that: The process parameters of electrospinning in step (3) are as follows: the distance from the double nozzle needle to the rotating receiving roller is 15 to 20 cm, and the injection speed of the spinning solution is 1 to 2 mL·h -1 The rotating speed of the rotating receiving roller is 300-500 r / min. -1 , voltage is 15~23kV, ambient temperature is 20~50℃, and ambient humidity is 10~40%.

10. The method for preparing a lithium metal composite negative electrode based on a one-dimensional nanoreactor according to claim 3, characterized in that: In step (4), the pre-oxidation temperature is 270-300°C, the time is 1-2h, and the heating rate is 1-5°C·min -1 .

Citation Information

Patent Citations

  • Self-supporting lithium metal negative electrode material and preparation method and application thereof

    CN112054203A

  • Electrode catalyst layer and membrane electrode assembly

    JP2024140554A

  • Multi-layer solid electrolyte separator for a lithium secondary battery and manufacturing method

    WO2022256837A1